Solutions for thermal energy exploitation from the exhaust of an industrial gas turbine using optimized bottoming cycles. (1st March 2020) - Sayyaadi, Hoseyn; Khosravanifard, Yaghoob; Sohani, Ali
Highlights: Different technologies for low-grade heat recovery were assessed. Kalina, Goswami, organic Rankine and trilateral flash cycles were investigated. The foremost optimized bottoming cycle for low-grade heat recovery was introduced. Sensitivity of the payback to economic factors were studied and evaluated. The minimum sold price for generated electricity of each cycles were determined. Abstract: The issues like depletion of fossil fuels and environmental concerns encourage policy makers to run different types of power plants, including gas-turbine power plants more efficiently. For this purpose, bottoming cycles can be employed to recover the low-grade thermal energy of the exhaust gases of the gas cycle. Kalina, organic Rankine, Goswami, and trilateral flash cycles were examined to be used as the second bottoming cycle of a gas-turbine power plant to scavenge low-grade thermal energy in the exhaust of an absorption refrigeration cycle as the first bottoming cycle. All alternatives to the secondary bottoming cycle were modeled and optimized by non-dominated sorting genetic algorithm II in MATLAB software considering energy and economic criteria. Then, the best alternative among optimized cycles was introduced. It was found that the best alternative is Goswami cycle, and the less desired one was Kalina cycle. Goswami cycle enabled to generate 4.26 MW of additional power as well as an additional 0.45 MW of an auxiliary cooling that reduces the required capacity of the chiller by 3.2%. The introduced foremost bottoming cycle increased the thermal efficiency of the power plant from 38.1 to 46.5%. The investments required for installation and usage of the best and worst bottoming cycle were determined to be paid back within 3.8 and 20.5 years, respectively. To have economic justification, the sold price of the best bottoming cycle (Goswami cycle) must be greater than 0.09 .(kWh) −1 on average.